Draught Animal Management and Welfare an important power source for marginal farmers - Panigrahy, Kuldeep Kumar; Panda, Sasmita; Behera, Kumaresh (Indian Farming, 2017)
Drought animal power has been used by man since time immemorial as it is a reliable and popular farm power resource. Thus, the management and welfare of draught animals is very important since they provide a source of power especially in agriculture and for other purposes in the village.